Answer:
When x = -3 y = -1
When x = -3/4 y = 7/2
Step-by-step explanation:
y = 4x^2 + 17x + 14
y = 2x + 5
Set each equation equal to each other
4x^2 + 17x + 14 = 2x + 5
Subtract 2x from each side
4x^2 + 17x-2x + 14 = 2x-2x + 5
4x^2 + 15x + 14 = 5
Subtract 5 from each side
4x^2 + 15x + 14-5 = 5-5
4x^2 + 15x +9 = 0
Factor
(4x+3) ( x+3) =0
Using the zero product property
4x+3 =0 x+3 =0
4x = -3 x=-3
x = -3/4 x=-3
Now we need to find y for each x
x =-3 y = 2x+5 =2(-3)+5 = -6+5 = -1
When x = -3 y = -1
x = -3/4 y = 2(-3/4) +5 = -3/2 +5 = 7/2
When x = -3/4 y = 7/2